MANAGEMENT OF ONLINE BASIC LEVEL OF LEVELED TRAINING FOR TO IMPROVE THE COMPETENCE OF EARLY CHILDHOOD AND CARE EDUCATION (ECCE) TEACHERS (Case Study at PP PAUD and DIKMAS West Java) - taufik rahman (IKIP Siliwangi Bandung, 2018)
Abstract The Center for Development of Early Childhood Education and Community Education (PP PAUD and Dikmas) West Java has programmed Online Basic Level of Leveled Training for Early Childhood and Care Education (ECCE) Teachers. The Leveled Training consists of basic, intermediate, and advance level which are constructed to improve the competence of three levels of ECCE teachers (junior assistance, assistance, and ECCE teachers), continuously and gradually. The online basic level training is supposed to provide junior assistant of ECCE teacher with minimum competency.The focus this study is to investigate how the management of online basic level training in improving the competence of ECCE teachers developed by PP PAUD and Dikmas West Java.The Purpose of this study is to describe the planning, implementation and evaluation of online basic level training in improving the competence of ECCE teachers. Supporting theories of this study are the management concept, training, online learning and competency of ECCE teachers.The methodology used in this study is descriptive qualitative with ex-post facto approach. The data obtained through analysis of documents and interviews with the organizer, instructor, mentor, administrator and alumni of Training. The subjects are five people consisting of the organizer, instructor, mentor, administrator and alumni of Training.Based on the analysis of data and discussion of research result, the findings are: (1) planning phase of online training was done with writing design, setting up learning media and tools, designing Content Management System (CMS) and Learning Management System (CMS); (2) Implementation of the online basic level Training employed three main strategies, i.e. face-to-face online, tutorials online and independent learning; (3) Evaluation of the online basic level Training was divided into two parts, the evaluation results include (a) cognitive, (b) affective (c) psychomotor, and program evaluation.Recommendations for the organizers are to increase server capacity, improve the Content Management System and Learning Management System, develop online intermediate and advance levels of leveled Training for improving the competence of ECCE teachers and develop other online trainings. Recommendation for the instructors and mentors are to provide more intensive enrichment of training materials, of operating IT and online activities, and completing of SOP of supervisors and mentors. Keyword : Management, online Training, ECCE teachers